Change in Organizational Culture: Change in Organizational Culture - Febiyola Wijaya (Jurnal Mantik, 2020)
Every individual, organization and culture in the world will always change. This study studies how the organizational culture of Be Like a Bee changes at PT. ILF, by looking at what values are instilled from the culture of Be Like a Bee, how is the internalization process and the role of the leader in socializing those values.This research is a type of descriptive research because it aims to provide an overview of the organizational culture changes Be Like a Bee that occurred in PT. ILF, what values are instilled, how the process of internalizing these values and the role of leaders in socializing it. The data analysis method used in this study is the grounded theory method. This method is an analytical method that combines scientific thinking and art. The values that are instilled include: hard work, work discipline, productivity and efficiency. The internalization process is carried out in various ways at the manager level and staff and non staff levels.